Assessing the production and marketing system of smallholder goat value chains in Davao Region, Philippines - Bangcaya, Exegesis Jedidiah E. (Banwa, 2019)
Goats are popular among Filipinos and can produce products such as meat, milk, and other value-added products. In the Philippines, the demand is greater than its supply. There are many opportunities for farmers and entrepreneurs to venture into goat raising and further processing of the products. Low productivity of the agricultural sector has contributed to increasing poverty, but with better productivity in goat production and marketing, farmers will be able to improve their livelihood. This study aims to map the existing goat value chains in the Davao Region and determine the financial viability and opportunities for value chain upgrading of smallholder goat farmers. This study utilizes the value chain mapping approach and net margins analysis in providing value chain upgrading recommendations geared towards the improvement of smallholder farmers. Results showed that the goat sector faces challenges on management, breeding activities, disease control, transportation cost, sources for superior breeds, insufficient forage supply and processing equipment, limited market information, and capital for inputs and expansion. It also showed that small-scale farmers are not able to maximize their income because of operational inefficiencies, whereas the commercial farmers and processors are able to profit significantly. The study suggest more government assistance not just in goat dispersal but also in marketing and value-adding activities, provision of more seminars and hand-on training, provision of grants for better access to forage and other facilities, formation of goat farmers' associations, and promotion of the industry to encourage more investors to further expand the goat sector.